2016
DOI: 10.1002/2015jg003306
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Fe(II) oxidation distinguished by long‐range correlation in redox potential

Abstract: The kinetics of bacterial Fe(II) - Index Terms0412 Biogeochemical kinetics and reaction modelling 0448 Geomicrobiology

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The variation between α values indicates that biological processes give rise to stronger correlation of time series measurements of fluctuations in redox potential in the systems studied here. This is consistent with results of correlation analysis recently reported for low biomass and high biomass circumneutral, microaerophilic Fe(II)oxidizing systems (Enright and Ferris, 2016), where the low biomass condition gave rise to a scaling exponent of 1.67, and the high biomass condition gave rise to a scaling exponent of 1.89 (Enright and Ferris, 2016).…”
Section: Biogeochemical Significancesupporting
confidence: 92%
“…The variation between α values indicates that biological processes give rise to stronger correlation of time series measurements of fluctuations in redox potential in the systems studied here. This is consistent with results of correlation analysis recently reported for low biomass and high biomass circumneutral, microaerophilic Fe(II)oxidizing systems (Enright and Ferris, 2016), where the low biomass condition gave rise to a scaling exponent of 1.67, and the high biomass condition gave rise to a scaling exponent of 1.89 (Enright and Ferris, 2016).…”
Section: Biogeochemical Significancesupporting
confidence: 92%
“…In more recent times, other studies have targeted the investigation of soil biogeochemistry and transient redox conditions caused by the water table fluctuations [20] and observed a decreasing soil Eh after the addition of glucose [21]. Enright et al [22,23] demonstrated a distinguishable biological signal by immersing a pair of electrodes in an iron-oxidizing biofilm. Graphite electrode experiments have also been used to investigate the rates of anaerobic microbial activity in a diversity of anoxic sediments [24].…”
Section: Introductionmentioning
confidence: 99%
“…While informative, these results only hint at the underlying mechanisms and bioenergetic capacity of FeOB to catalyze otherwise spontaneous abiotic Fe(II) oxidation rates. More recently, the statistical dependence (i.e., long-range correlation, also known as memory or persistence) of temporal fluctuations in electrochemical measurements of redox potential on a time scale of minutes to seconds were found to distinguish bacterial and abiotic Fe(II) oxidation 7,25 . Long-range correlation in a time series implies that any measured value is statistically dependent on preceding values, and can take the form of positive correlation (a past increasing trend will continue to increase into the future) or negative correlation (an increasing trend is likely to be followed by a decreasing trend) 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Long-range correlation in a time series implies that any measured value is statistically dependent on preceding values, and can take the form of positive correlation (a past increasing trend will continue to increase into the future) or negative correlation (an increasing trend is likely to be followed by a decreasing trend) 26,27 . Such correlative dependence has proven to be consistently more pronounced for bacterial Fe(II) oxidation than abiotic Fe(II) oxidation 25 ; thus, the parameter of correlation strength, measured by detrended fluctuation analysis (DFA) scaling exponents ( α ), can feasibly be used to distinguish microbially-catalyzed Fe(II) oxidation from homogenous and heterogeneous chemical oxidation. This new approach to investigating bacterial Fe(II) oxidation is compelling in light of the fact that the Gibbs free energy (Δ G r ) of an oxidation-reduction reaction is an explicit thermodynamic function of redox potential.…”
Section: Introductionmentioning
confidence: 99%